Sustainable Corporate Governance and Stakeholder Engagement: Analyzing the Role of Stakeholder Integration in ESG Reporting - Čufar, Matic; Primec, Andreja; Belak, Jernej (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Aim: This research paper focuses on the identification and comparison of stakeholder reporting in practice. It covers the recognition of key stakeholders, identification of channels of dialogue, and the integration of stakeholder interests into corporate governance. Methodology: A content analysis methodology has been used to conduct research on stakeholder reporting by selected companies. Based on the research results, a comparative analysis has been carried out to examine which ESG reporting areas contain the most detailed stakeholder-related disclosures and to what extent companies include the interests of their key stakeholders in their corporate governance. Findings: Based on the research results, it can be concluded that companies include the interests of key stakeholders in the process of sustainable management and corporate governance. The inclusion of key stakeholders is particularly evident in terms of their identification, the gathering of information, and the formation of groups of key activities relevant to the company. Value: The main value of this research paper lies in gaining additional insights into the inclusion of key stakeholders in corporate governance and sustainability reporting in practice. It provides further understanding of the areas related to key stakeholder engagement and offers potential recommendations for the continued inclusion of stakeholders.